A theoretical approach to analyse the importance of Government and non-governmental organisations' roles in lowering adolescent depressive symptoms in Orissa with hearing loss (Journal of Advances and Scholarly Researches in Allied Education, 2023)
It is possible that hearing loss contributes to the development of some symptoms often associated with ageing, such as the inability to keep up with discussions, withdrawing from social engagements, and the formation of moderate paranoid tendencies. There may also be a connection between hearing loss and some depressive symptoms.There is a cluster of symptoms that all sufferers of depression share. Symptoms include persistent feelings of melancholy, worry, or emptiness, along with hopelessness or pessimism that last for weeks at a time.A connection between the two is obvious; depressed people often have trouble hearing. It is common for people with hearing loss to have trouble communicating, which may lead to frustration, exhaustion, and isolation. Research has linked being lonely to feeling down and depressed.